The art of democracy : a concise history of popular culture in the United States. - Cullen, Jim, 1962- (Monthly Review Press, 2002)
The highly acclaimed first edition of The Art of Democracy won the 1996 Ray and Pat Brown Award for ""Best Book, "" presented by the Popular Culture Association.